Medical device manufacturers preparation for the new Medical Device Regulation (MDR) - Huusko, Juhamatti; Kinnunen, Ulla-Mari; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2020)
There is an increasing number of medical devices on the market that help health care providers to diagnose and treat patients. In addition, patients can use medical devices for self-care purposes. This requires legislators to update legislation. One of the main purposes of the legislation is to ensure patient safety. In 2017, the European Parliament and the Council adopted the Regulation (2017/745) on Medical Device Regulation (MDR), which entered into force in May 2017. It has a transitional period until May 2020, and it replaces the former Medical Devices Directive (93/42/EEC). The purpose of this study was to find out what kind of information the medical device manufacturers in Finland have about the new Medical Device Regulation (2017/745) and how they obtain information. The sample data was collected by a questionnaire in April 2019. The questionnaire was created with Webropol software and sent directly to the recipients (N=287). In addition, the questionnaire was shared in social media. In total, 60 participants responded to the questionnaire. This study showed that information on the new Medical Device Regulation (2017/745) is fragmented and companies need to find information from multiple sources. However, companies state that the information is available and the level of knowledge among companies is good. Companies acquire a significant amount of knowledge through self-study, but they also receive more information by attending training organized by Healthtech Finland and expert companies, which provide regulatory services. Larger companies are better prepared for the regulation than the smaller companies. Based on these results, the original timetable for the new Medical Device Regulation (2017/745) was challenging. Quarter of the companies involved in this study had medical devices registered in the UK.